A Review of Abattoir Reflexes in Relation to Anaerobic Glycolysis and Meat Quality - Swatland, Howard J. (European Journal of Applied Sciences, 2024)
Current research on meat quality is dominated by correlative studies of animal genotypes and histochemical fibre types, correlating features of live animals with features of commercial importance in their meat. But between live muscle and meat, there is an epigenetic realm where random factors mediated by animal treatments and their nervous systems may have strong effects. They have the potential to obscure real correlations between live animals and meat quality, or to produce spurious correlations. Physiological studies in abattoirs may prove things one way or the other.